Comunicación, números y marketing - Rodríguez Cisneros, Erick Rafael (2021)
At the university I´d learned all the theory, with joy because i liked it and understood it, because I´d grown up believing that the letters and only the letters were my stuff, so i grew up keeping distance and the necesary relation with numbers. Later, when i finished university, i began to work in different sectors and learned everything that the university didn´t teach me, for example, i learned to understand numbers, their importance, their omnipresence, the advantages of knowing and working with them; and it's not that i have a particular tendency or fondness for statistics, I just think that I´ve managed to reach a better understanding of how numbers can communicate, sometimes even better than ourselves, and this is something that I always try to transmit and teach.